Individual Differences in the Recognition of Enjoyment Smiles: No Role for Perceptual–Attentional Factors and Autistic-Like Traits - Manera, Valeria; Del Giudice, Marco; Grandi, Elisa; Colle, Livia (Frontiers in Psychology, 2011)
Adults show remarkable individual variation in the ability to detect felt enjoyment in smiles based on the Duchenne marker (AU6). It has been hypothesized that perceptual and attentional factors (possibly correlated to autistic-like personality traits in the normative range) play a major role in determining individual differences in recognition performance. Here, this hypothesis was tested in a sample of 100 young adults. Eye-tracking methodology was employed to assess patterns of visual attention during a smile recognition task. Results indicate that neither perceptual-attentional factors nor autistic-like personality traits contribute significantly to individual differences in smile recognition.